An IoT-based smart home prototype: Enhancing energy efficiency, water conservation, and sustainability education - Wildan Arasid; Diky Zakaria; Cep Ubad Abdullah (Education and Development Research, 2025)
The rapid development of the Internet of Things (IoT) has driven the emergence of smart home innovations that not only provide convenience but also contribute to energy efficiency and resource conservation. This study aims to develop an IoT-based smart home prototype using the ESP8266-12e module to control lights and solenoid valves that function as water faucets. The system operates in two modes: automatic mode, utilizing light-dependent resistors (LDRs) and ultrasonic sensors, and manual mode through a web-based control interface. The method in this study uses an experimental method consisting of a literature review, hardware and software design, implementation, and testing. The results show that the system functions reliably and remains stable within a Wi-Fi connection range of up to 21 meters. Furthermore, this prototype shows potential as a project-based learning medium in science and technology education, particularly in the context of sustainability education. By integrating the concepts of electricity and water conservation, this study contributes to increasing scientific literacy while supporting sustainable household practices.